THE ROLES OF DEMOGRAPHIC FACTORS ON SOCIAL ENTREPENEURSHIP INTENTION IN MALAYSIA - Siti Daleela Mohd Wahid; Shafinar Ismail; Hazrel Moktar; Wan Mohd Hirwani Wan Hussain; Abu Hanifah Ayob (Asia-Pacific Journal on Religion and Society, 2022)
Social entrepreneurship (SE) is an innovative entrepreneurial approach gaining great interest from many parties due to its significant effects on the social and economic transformation. However, the current prevalence rate among Malaysian involving in SE recorded at the lowest level comparing to the neighboring countries like Singapore and Thailand. As suggested by previous literature, to investigate the factors lead to the issue,  first step, we need to identify the profiling characteristics of the citizen who can be the potential social entrepreneurs. Therefore, the purpose of this paper is to determine the demographic characteristics such as gender, age, category of institution and duration of being involve in SE-based program with the SE intention. We used stratified sampling technique to select the sample of 419 university students. The data was analyzed by using SPSS version 25. We proposed four hypotheses to be tested and surprising, there is a significant difference between category of institutions and SE intention. It is affirmed that students from public institutions has high intention to be a social entrepreneur as compared to students from private universities. Moreover, gender, age and duration of being involve in SE-based program have no significant difference towards student’s SE intention. Discussion  were made. Lastly, limitations of this paper as well as future research directions were enunciated clearly.